Rapid heparinization as a decisive strategy for acute upper limb ischemia: a case report - Veliawan, Zhafran; Kurnianingsih, Novi (Universitas Brawijaya, 2025)
Background: Acute upper limb ischemia is a rare clinical presentation of thromboembolism, mostly known in patients with atrial fibrillation. Both conservative and surgical procedures are available as alternatives to therapy. In this case report, a patient who had been diagnosed with acute upper limb ischemia received immediate heparin administration in order to protect the upper limb and restore its functional capabilities. Case Illustration: A 60-year-old male presented with acute pain and numbness, along with bluishness and a cold sensation in the right hand. He has unrestricted arm mobility. The patient has a medical background of atrial fibrillation for over 11 years. The right hand exhibited reduced peripheral saturation, pulselessness, pain, pallor, and poikilothermy, but neither paresthesia nor paralysis. Duplex ultrasonography showed no detectable blood flow from the right brachial artery up to the distal arteries. However, the vein remained audible. The patient received heparinization immediately. Conclusion: Immediate identification and administration of heparin in instances of acute upper limb ischemia (AULI) are crucial for achieving favorable outcomes and a good prognosis. Continued treatment with anticoagulants is necessary for the therapeutic intervention in order to enhance limb preservation, minimize complications, and ensure patients have an excellent quality of life subsequent to conservative treatment.